Antitobacco advertising and lung cancer stigma: a qualitative study of the experiences of people with a lung cancer diagnosis. Issue 1 (2nd January 2022) - Rose, Shiho; Boyes, Allison W.; Kelly, Brian; Bridge, Paula; Carlson, Melissa; Coutts, Emily; Paul, Chris
Abstract : Abstract: Stigma is often experienced by people affected by lung cancer due to the known links between lung cancer and smoking. Antitobacco campaigns, although attempting to "de-normalise" smoking, may contribute to stigmatising people affected by cancer. The study examined how people diagnosed with lung cancer recall and respond to antitobacco advertisements postdiagnosis. Sixteen qualitative semi-structured interviews were conducted with people with a lung cancer diagnosis who were recruited from an Australian clinical cancer registry. Interviews were analysed using thematic analysis. Participants mostly recalled narrative style antitobacco advertisements. A wide array of emotional responses to the advertisements were reported, including relief, shame, worry, discomfort, and resignation. Some participants avoided the advertisements altogether. Although some participants found the advertisements to be promoting stigma, others did not. Participants were not opposed to the broadcasting of antitobacco advertisements. Rather, the advertisements were perceived as appropriate and necessary. In conclusion, although people diagnosed with lung cancer reported experiencing some negative emotional responses to antitobacco advertising, they were supportive of its continuance.